Emotional intelligence and anxiety in women - Paloma Gil-Olarte; Rocío Gómez-Molinero; Paula Ruiz-González; Rocio Guil (INFAD, 2019)
The Report of the Fourth World Conference on Women (United Nations, 1995) declares the right to enjoy full physical and mental health, understood as a state of emotional, social and physical well-being. Following these principles, the Women